A cascade reaction of o-alkenylphenyl carbodiimides with isocyanides by copper catalysis: direct construction of 4, 5-dihydroimidazo[1, 5-a]quinazolines. Issue 37 (14th September 2016) - Hao, Wenyan; Sang, Xiaoyan; Xiao, Yunsheng; Cai, Mingzhong
Graphical abstract: Highlights: A CuI-catalyzed cascade reaction of carbodiimides with isocyanides was reported. The skeleton of 4, 5-dihydroimidazo[1, 5- a ]quinazoline was first synthesized. In this transformation, multi-bonds and two new rings were formed in one pot. The tandem addition–cyclization is a good strategy for synthesis of N- heterocycles. Abstract: An efficient method for the synthesis of 4, 5-dihydroimidazo[1, 5- a ]quinazolines derivatives by copper catalyzed cascade reaction of o -alkenylphenyl carbodiimides with isocyanides has been developed. Moderate to good yields could be obtained by using CuI as the catalyst and K3 PO4 as the base. This reaction initially proceeds through a formal [3+2] cycloaddition and followed by intramolecular conjugate addition annulation.